Expression of adenovirus type 2 late genes in HeLa cells infected with adenovirus type 2 or adenovirus type 2-simian virus 40 hybrid viruses. - Lawrence, C B (1981)
The relative levels of expression of the five 3'-coterminal mRNA families encode in the 16.4 to 99 map unit transcription unit of adenovirus type 2 (Ad2) are determined in part by the frequency of utilization of five possible polyadenylation sites. The possibility that polyadenylation frequencies at these sites may be regulated was tested by examining the expression of the fiber (polypeptide IV) gene in cells infected with nondefective (ND) Ad2-simian virus 40 hybrid viruses which express a sixth late mRNA family. Both the relative rate of fiber protein synthesis and the relative abundance of fiber mRNA were normal in cells infected with the hybrid viruses Ad2+ND1, Ad2+ND2, or Ad2+ND4.